MULTIMEDIA DEVELOPMENT TO INTRODUCE ENGLISH VOCABULARY IN KINDERGARTEN - Danang Prasetyo (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2019)
Introducing english vocabularies in early childhood education institution generally has not used the media learning as well, incorrect pronountiation and spelling of the teacher also monotonous method. This research aimed to know multimedia feasiblity of english vocabulary introduction for group B at TK Wahidiyah Kota Kediri, knowing multimedia effectiveness of english vocabulary introduction for group B at TK Wahidiyah Kota Kediri. Field development used one group pretest posttest design. Instruments used in data collection are questionnaire, guidelines and interview guidelines which analized using descriptive technic, statistic descriptive and descriptive inferential. To know the effect of multimedia, analyzed by using the calculation with the help of software (software) that is SPSS 20. Based on result of t-test, known significance obtained by 0,00 which means smaller than the significance used in this research that is 0 , 05, then H0 is rejected and Ha accepted. Based on the results of research can be concluded that the development of multimedia for the introduction of English vocabulary effect on the introduction of English vocabulary in children group B TK Wahidiyah Kota Kediri preliminary